2016
DOI: 10.1186/s12864-016-2979-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to assessing bisphenol-A hazards using an in vitro model system

Abstract: BackgroundAlthough the toxicological impacts of the xenoestrogen bisphenol-A (BPA) have been studied extensively, but the mechanism of action is poorly understood. Eventually, no standard method exists for evaluating the possible health hazards of BPA exposure. Considering mice spermatozoa as a potential in vitro model, we investigated the effects of BPA exposure (0.0001, 0.01, 1, and 100 μM for 6 h) on spermatozoa and the related mechanisms of action. The same doses were also employed to evaluate protein prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(92 citation statements)
references
References 47 publications
6
82
4
Order By: Relevance
“…This observation confirms the likelihood of BPS-mediated disruption of epigenetic modulation. In addition to steroidogenesis and epigenetics, cytoskeletal and associated factors (tubulin α-1B chain, talin-1, Ser/Thr-protein phosphatase 2A) are affected and considerably affiliated with other findings on cytoskeletal structures, accordingly with previous studies on BPA (Rahman et al 2016).…”
Section: Discussionsupporting
confidence: 75%
“…This observation confirms the likelihood of BPS-mediated disruption of epigenetic modulation. In addition to steroidogenesis and epigenetics, cytoskeletal and associated factors (tubulin α-1B chain, talin-1, Ser/Thr-protein phosphatase 2A) are affected and considerably affiliated with other findings on cytoskeletal structures, accordingly with previous studies on BPA (Rahman et al 2016).…”
Section: Discussionsupporting
confidence: 75%
“…Different parts of the female reproductive tract, such as the uterus, uterotubal junction, and oviduct, are specifically programmed to select only a functionally mature spermatozoon for fertilization (Holt and Fazeli, 2010). Once the spermatozoa reach the oviduct, they temporarily attach to the isthmus epithelium to undergo capacitation before ovulation (Rahman et al, 2015(Rahman et al, , 2016. Capacitation is a process during which complex molecular, biochemical, and physiological changes occur in spermatozoa in the female reproductive tract or in in vitro specialized media and is a prerequisite for fertilization (Salicioni et al, 2007;Visconti, 2012;Kwon et al, 2015).…”
Section: Response To Stressmentioning
confidence: 99%
“…Identification and quantification of genes/proteins in a cell provides fascinating insights regarding their cellular functions. Genomics deals with the structure, function, evolution, and mapping of genomes (Bader et al, 2003), whereas proteomics involves novel approaches for characterizing proteins by performing qualitative and quantitative analyses (Rahman et al, 2016(Rahman et al, , 2017a(Rahman et al, , 2018. A spermatozoon provides half of the nuclear genetic material to the diploid offspring via fertilization.…”
Section: Genomic and Proteomic Contents Of X And Y Spermatozoamentioning
confidence: 99%
“…Previous studies have shown that BPA, at both high and low concentrations, has marked effects on growth, maintenance and apoptosis related signaling in various cell types, including male germ cells 10 13 . Moreover, BPA has been shown to have vertically transferred effects on spermatozoa of F1 mice following exposure in gestational period 14 , and effects on spermatozoa in vitro 15 .…”
Section: Introductionmentioning
confidence: 99%